Is a Global Warming E-Book Based on Problem-Based Learning Assisted by PhET Interactive Simulation Effective in Enhancing Students’ Communication Skills? - Ulfa, Siti Maryam; Kuncoro Asih Nugroho; Aldila, Febri Tia; Jumadi; Nurdiyanti; Abidaturrosyidah (Journal of Education Technology, 2024)
One of the important skills that must be mastered in 21st-century learning is communication skills. The facts show that students' communication skills in learning physics, specifically on the topic of global warming, are still low. This research aims to determine the feasibility and effectiveness of the global warming e-book based on problem-based learning (PBL) assisted by PhET interactive simulation to improve students' communication skills. The type of research used is pre-experimental, with a one-group pretest-posttest research design. The sampling technique is cluster random sampling, the modeling class and the implementation class are randomly selected. This research was conducted on 55 students in class X of high school, consisting of 32 students in the modeling class and 23 students in the implementation class. Data collection techniques are carried out through validation and pretest-posttest. The validation data to determine the feasibility of e-books and communication ability test instruments were analyzed using the V 'Aiken equation. The effectiveness was analyzed using the N-Gain test and to determine the significance of the increase using the ANOVA test with eta squared (effect size) analyzed with the SPSS program. The results of the study show that the validity of the e-book is on very good criteria, so it is worth using. The results of the N-Gain test of the modeling class and the implementation class showed that the use of e-books was quite effective in improving students' communication skills, with an impact size of 0.406 in the modeling class and 0.519 in the implementation class. So, this global warming e-book can be used by physics teachers in physics learning. The limitations of this study include the use of subjects limited to only two classes and restricted time allocation. Therefore, future research is expected to conduct studies on a larger scale and consider time allocation when selecting the learning model.